Photovoltaic-Driven BLDC Motor with Advanced Converter and MPPT Technique for Sustainable Water Pumping Solutions - Rishikesh, N.; Gomathi, V.; Rakesh, V.; Vijayalakshmi, R.; Robin, Cinu S; Kaliappan, Kannan (2025 Global Conference in Emerging Technology (GINOTECH), 2025)
The integration of solar Photovoltaic (PV) systems with Brushless DC (BLDC) motors for water pumping applications provide a sustainable, cost-effective solution to energy needs in rural areas. Henceforth, this paper presents a Modified Quadratic Boost Converter (MQBC) designed for increasing the voltage level from the PV array, acting as an intermediate DC-DC converter. Additionally, a novel Lyrebird Optimized Algorithm (LOA) based Maximum Power Point Tracking (MPPT) controller is introduced for continuously adjusting the controlling point to capture the maximum available energy from the PV panels. The Voltage Source Inverter (VSI)-driven BLDC motor powers the centrifugal water pump, reducing high-frequency switching losses and improving system efficiency. Simulations using MATLAB- Simulink validate the system's superior performance, demonstrating that the converter achieves a high efficiency of 95.2% in power conversion, optimizing the energy output for water pumping systems.